"It's Always Good to Ask": A Mixed Methods Study on the Perceived Role of Sexual Health Practitioners Asking Gay and Bisexual Men About Experiences of Domestic Violence and Abuse. (April 2018) - Bacchus, Loraine J.; Buller, Ana Maria; Ferrari, Giulia; Brzank, Petra; Feder, Gene
Development of joint displays is a valued approach to merging qualitative and quantitative findings in mixed methods research. This study aimed to illustrate a case series mixed methods display and the utility of using mixed methods for broadening our understanding of domestic violence and abuse. Using a convergent design, 532 gay and bisexual men participated in a Health and Relationship Survey in a U.K. sexual health service and 19 in an interview. Quantitative and qualitative data were analyzed separately and integrated at the level of interpretation and reporting. There were inconsistencies in perceptions and reports of abuse. Men were supportive of selective enquiry for domestic violence and abuse by practitioners (62.6%; 95% confidence interval = 58.1% to 66.7%) while being mindful of contextual factors.